2010
DOI: 10.1038/eye.2010.90
|View full text |Cite
|
Sign up to set email alerts
|

The effect on visual function of Hydroview intraocular lens opacification: a cross-sectional study

Abstract: This study highlights the significant impact IOL opacification has on visual performance and experience, in particular glare and consequent impact on quality of life. The study shows that to quantify accurately the effect of IOL opacification on vision glare must be assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…This observation helps explain why patients with opacified IOLs do not necessarily have a measurable decrease in visual acuity but the symptoms prompting explantation are, in many cases, dominated by disability glare. 2,3 In summary we report for the first time, to our knowledge, measurements of light scattering and light transmittance in a relatively large number of opacified IOLs associated with a significant decrease in visual function and requiring IOL explantation. A Scheimpflug system and a spectrophotometer were used for the measurements of light scattering and the percentage of light transmittance, respectively.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This observation helps explain why patients with opacified IOLs do not necessarily have a measurable decrease in visual acuity but the symptoms prompting explantation are, in many cases, dominated by disability glare. 2,3 In summary we report for the first time, to our knowledge, measurements of light scattering and light transmittance in a relatively large number of opacified IOLs associated with a significant decrease in visual function and requiring IOL explantation. A Scheimpflug system and a spectrophotometer were used for the measurements of light scattering and the percentage of light transmittance, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…2,3 Conceivably, the quality of vision loss in these patients is mostly related to increased light scattering caused by the small calcified deposits inside or on the optic surface. [2][3][4][5] However, only a handful of studies have assessed light scattering and transmittance in calcified IOLs requiring explantation. 4,6,A Currently available literature on light scattering and transmittance of IOLs with postoperative optic changes is generally limited to glistenings or increased surface light scattering (referred as to whitening by Japanese colleagues); explantation has been rarely reported in association with these conditions.…”
mentioning
confidence: 99%
“…16,17 The forward light scattering measurements and subsequently the stray light would provide a meaningful correlation with possible clinical symptoms related to glare disability and stray light hindrance. [13][14][15] Therefore, in the current study forward light scatter, stray light, and other optical quality/performance indicators were also assessed for lenses explanted because of clinically significant opacification. Both the back and forward light scattering were significantly increased in the explanted lenses, which resulted in the reduction of light transmission, MTF, and Badal image contrast for the opacified lenses.…”
Section: Discussionmentioning
confidence: 99%
“…3 Clinical studies on opacified IOLs demonstrated that they may be more associated with complaints of glare and ''foggy'' or ''cloudy'' vision, while visual acuity is not drastically reduced. 13,14 The quality of vision loss in affected patients appears to be predominantly related to increased forward light scattering and subsequently retinal stray light, which can give rise to a variety of subjective complaints, including glare in various illuminating conditions, halos around bright lights, color and contrast loss, as well as hazy vision. 15 These symptoms may prompt IOL explantation even in the absence of measurable decrease in visual acuity.…”
mentioning
confidence: 99%
See 1 more Smart Citation